Palaeo-Eskimo genetic ancestry and the peopling of Chukotka and North America - Flegontov, Pavel; Altınışık, N Ezgi; Changmai, Piya; Rohland, Nadin; Mallick, Swapan; Adamski, Nicole; Bolnick, Deborah A; Broomandkhoshbacht, Nasreen; Candilio, Francesca; Culleton, Brendan J; Flegontova, Olga; Friesen, T Max; et al. (Nature, 2019)
Much of the American Arctic was first settled 5,000 years ago, by groups of people known as Palaeo-Eskimos. They were subsequently joined and largely displaced around 1,000 years ago by ancestors of the present-day Inuit and Yup'ik1-3. The genetic relationship between Palaeo-Eskimos and Native American, Inuit, Yup'ik and Aleut populations remains uncertain4-6. Here we present genomic data for 48 ancient individuals from Chukotka, East Siberia, the Aleutian Islands, Alaska, and the Canadian Arctic. We co-analyse these data with data from present-day Alaskan Iñupiat and West Siberian populations and published genomes. Using methods based on rare-allele and haplotype sharing, as well as established techniques4,7-9, we show that Palaeo-Eskimo-related ancestry is ubiquitous among people who speak Na-Dene and Eskimo-Aleut languages. We develop a comprehensive model for the Holocene peopling events of Chukotka and North America, and show that Na-Dene-speaking peoples, people of the Aleutian Islands, and Yup'ik and Inuit across the Arctic region all share ancestry from a single Palaeo-Eskimo-related Siberian source.
Keywords: Afrika; History, Ancient; alely; fylogeografie; genom lidský; Human Migration; analýza hlavních komponent; Arktida; Phylogeography; Alleles; Arctic Regions; Canada; Europe; Evropa; Kanada; Haplotypes; Asia, Southeastern; Genome, Human; dějiny starověku; Sibiř; Principal Component Analysis; Aljaška; Inuité; Africa; Inuit; Humans; jihovýchodní Asie; migrace lidstva; fylogeneze; Alaska; haplotypy; Siberia; Phylogeny; lidé